Tips to Optimize Management of Tibial Plateau Fractures Offered - Kuznar, Wayne (MD Conference Express, 2014)
The available evidence and surgical techniques that can be applied to the management of tibial plateau fractures, including unusual variants of these injuries, is addressed in this article.